2018
DOI: 10.1590/s2175-97902018000001003
|View full text |Cite
|
Sign up to set email alerts
|

Active ingredients, mechanisms of action and efficacy tests of antipollution cosmetic and personal care products

Abstract: Urban population around the globe is direct exposed to the pollution caused by several sources (vehicles, industries, smokes etc.) and primary pollutants are divided in particulate matter and toxic gases. Current researches in populous countries indicated that exposure to pollution could affect sebum composition, stratum corneum quality and signs of skin aging. Hair and scalp are also affected by the excessive exposure to pollutants, resulting in a dull, dry and lifeless appearance. Cosmetics have been evolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Among a large number of flavonoids, rutin is remarkable for its expressive properties to antagonize the increase in capillary fragility, to reduce high blood pressure, to protect plants against direct and indirect influences of UV radiation and to show antioxidant actions against a wide range of free radicals. In addition, not been detected in vitro cutaneous penetration of the rutin incorporated in a cosmetic emulsion (VELASCO et al, 2018;Bondarev & Knyukshto 2013). The chromophoric nature of flavonoids, such as rutin, are similar of UV organic filters and can be responsible for prevention of UV radiation damage to a variety of plants.…”
Section: Structuralmentioning
confidence: 99%
“…Among a large number of flavonoids, rutin is remarkable for its expressive properties to antagonize the increase in capillary fragility, to reduce high blood pressure, to protect plants against direct and indirect influences of UV radiation and to show antioxidant actions against a wide range of free radicals. In addition, not been detected in vitro cutaneous penetration of the rutin incorporated in a cosmetic emulsion (VELASCO et al, 2018;Bondarev & Knyukshto 2013). The chromophoric nature of flavonoids, such as rutin, are similar of UV organic filters and can be responsible for prevention of UV radiation damage to a variety of plants.…”
Section: Structuralmentioning
confidence: 99%
“…Striking evidence has demonstrated that air pollution can cause severe damage to human skin, triggering disorders such as inflammatory reactions, allergies, skin aging and cancer, due to alterations in physiological parameters that impact skin health [1][2][3][4]. In this regard, there is increasing consumer demand for cosmeceuticals based on natural products with the aim to improve skin beauty and protect skin from environmental insults [5][6][7][8]. A common pathway to identify promising sources of active phytochemicals involves the search for plant species traditionally used in folk or traditional medicine.…”
Section: Introductionmentioning
confidence: 99%
“…However, since photodamage can be generated by different mechanisms [11], other agents such as antioxidants have recently been added to improve the photoprotection efficacy of photoprotective products [12]. This requirement for mitigating UV-induced skin damage might explain the growing demand for topically applied biologically active ingredients [13,14]. Considering the limitations regarding UV filters toxicity (for both human and environmental health) and their partial photoprotection capability, there is a reasonable demand to find new photoprotectants.…”
Section: Introductionmentioning
confidence: 99%